The Psycholinguistic Effects of Blackboards and Colorful Chalk on Arabic Vocabulary Acquisition in Malaysian - Muhamad Solehudin; Nur Hanifansyah; Masnun; Yusuf Arisandi; Menik Mahmudah; Syarif Muhammad Syahed (Arabic Education Department, Islamic Studies Faculty, Universitas Muhammadiyah Malang, 2025)
This study explored the psycholinguistic effects of blackboards and colorful chalk on Arabic vocabulary acquisition at Maktab Mahmud Yan, Malaysia. Using a mixed-methods approach involving 60 students through surveys, interviews, and classroom observations, the study found that this low-tech, visually engaging method significantly improved vocabulary retention, enhanced motivation, and fostered collaborative learning. Remarkably, the initiative continued even after the departure of Indonesian instructors, supported by remote guidance and periodic visits. This research provides a novel contribution by demonstrating that traditional tools, when used creatively and cooperatively, can achieve outcomes comparable to digital solutions. It highlights the potential of multisensory, student-centered strategies in cross-cultural and under-resourced educational environments.